(untitled) (Journal of The Colloquium for Information Systems Security Education, 2020)
The design of a gamified instructional paradigm requires careful identification of concepts, concept dependencies, and concept flow in order to achieve maximum student proficiency, in a subject matter, while maintaining engagement. This is especially true for difficult and counter-intuitive fields such as quantum cryptography. In this paper, we present an abstraction of concepts that are needed to learn quantum key distribution in a gamified environment. This is coupled with a powerful adaptive navigation algorithm that guides students from one exercise to the next in the game such that maximum proficiency is achieved in various concepts associated with each exercise. The student traverses through different lessons in the game achieving the lesson outcomes in an efficient manner. This represents the first of its kind abstraction of quantum cryptography concepts and a navigation algorithm for a gamified paradigm.